Underresolved absorption spectroscopy of OH radicals in flames using broadband UV LEDs. (April 2018) - White, Logan; Gamba, Mirko
Highlights: A broadband UV LED absorption diagnostic has been developed and described. The technique uses underresolved spectral measurements. It is demonstrated for combustion applications in premixed methane/air flames. An uncertainty model for underresolved spectroscopy is applied. The correlated nature of simultaneous property measurements is discussed. Abstract: A broadband absorption spectroscopy diagnostic based on underresolution of the spectral absorption lines is evaluated for the inference of species mole fraction and temperature in combustion systems from spectral fitting. The approach uses spectrally broadband UV light emitting diodes and leverages low resolution, small form factor spectrometers. Through this combination, the method can be used to develop high precision measurement sensors. The challenges of underresolved spectroscopy are explored and addressed using spectral derivative fitting, which is found to generate measurements with high precision and accuracy. The diagnostic is demonstrated with experimental measurements of gas temperature and OH mole fraction in atmospheric air/methane premixed laminar flat flames. Measurements exhibit high precision, good agreement with 1-D flame simulations, and high repeatability. A newly developed model of uncertainty in underresolved spectroscopy is applied to estimate two-dimensional confidence regions for the measurements. The results of the uncertainty analysis indicate that the errors in the outputs of the spectral fitting procedure are correlated. The implications of the correlation between uncertainties for measurement interpretation are discussed.